THE JURISPRUDENCE OF THE COMMITTEE ON THE RIGHTS OF PERSONS WITH DISABILITIES AND ITS IMPLICATIONS FOR AFRICA (African Disability Rights Yearbook, 2021)
The Optional Protocol to the Convention on the Rights of Persons with Disabilities (CRPD), adopted by the United Nations (UN) and entered into force at the same time as the Convention, is a crucial addition to the international system of human rights protection.1 The Protocol provides for a mechanism for individual complaints to be submitted to the Committee on the Rights of Persons with Disabilities (CRPD Committee) by or on behalf of individuals or groups of individuals who believe that their rights under the CRPD have been violated by the state party. The Protocol gives persons with disabilities who are victims of such violations a voice and makes states more responsive and accountable to their obligations under the CRPD. The communication procedures of the Protocol are like those of other UN human rights treaty systems.2 The CRPD, along with its Optional Protocol, has been strongly embraced by African states. This is evidenced by the fact that, as of July 2016,42 African states have ratified the CRPD and 23 states are party to the Optional Protocol.4 This commentary seeks to, first, describe and critically discuss the emerging jurisprudence of the CRPD Committee. The focus will be on the communications where the Committee has to date found violations of the CRPD, namely, HM v Sweden, Szilvia Nyusti and PéterTakács v Hungary, Marie-Louise Jungelin v Sweden,Liliane Gröninger v Germany, SC v Brazil and Zsolt Bujdosó & 5 Others v Hungary. Akin to their counterparts in other regions, most African countries face significant challenges in formulating, domesticating and implementing disability rights to make the rights guaranteed in the CRPD a reality for persons with disabilities on the continent. The commentary further explores the implications for the African region, where the emerging jurisprudence of the CRPD Committee may offer guidance to state parties in the interpretation and implementation of rights.
Keywords: Convention on the Rights of Persons with Disabilities; Optional Protocol; jurisprudence; CRPD committee; violations of CRPD; challenges formulating, domesticating and implementing disability rights